EFFECTS OF INTEREST RATE ON HOUSING PRICES IN KENYA - Koome , Rodrick; Njaramba, Stephen (International Journal of Economics, 2022)
Purpose: The objective of the study was to examine the effect of interest rate on housing prices in Kenya. Methodology: The study used annual quantitative data for period 1960 to 2017. It employed Nonlinear Autoregressive Distributed Lag (NARDL) in determining the effects of negative and positive series of interest rates on housing prices. Findings: A non-linear relationship between interest rates and housing prices was confirmed. Both the negative series and positive series of interest rate portrayed a negative effect on housing prices in short run. For long run, positive series have positive effect on housing prices while the negative series have negative effect. Unique Contribution to Theory, Practice and Policy: A completely developed theoretical model putting together all meaningful inter-linkages between macroeconomic variable and price of housing is absent. The only ultimate way to address the issue is through empirical means. The findings indicate the presence of a non-linear relationship between interest rate and housing prices. The Central Bank of Kenya can change the Central Bank Reference rate (CBR rate) to alter the cost of money and consequently housing prices. In formulating a policy change, the Central Bank of Kenya should be cognizant of both the non-linear relationship existing between interest rates and prices of housing and the different magnitudes of effect of the positive and negative series on housing prices. When housing prices increase, either an increase or decrease the interest rate by the CBK will result to a downward movement in prices of housing in the short run, but at higher magnitude from the interest rate decrease. For the long-run, a decrease in interest rate will decrease housing prices, making housing affordable and improving the standards of living for citizens. Any upward movement in interest rate will result to a long-run increase in housing prices making housing more expensive and consequently out of reach of most citizens.